Positional Antagonism of Subjects of Tax Relation - Bobrova, A. V. (International Journal of Economics and Financial Issues, 2016)
The subject of the research is the relationship and also processes and mechanisms of interaction of subjects of tax relations concerning payment of taxes, distribution of powers during tax audits and investigative measures in the case of signs of committing tax crimes. The purpose of this research is to create a model of interaction of subjects of tax legal relations on the recommendation basis. To achieve the purpose is necessary in order to carry out the following tasks: to analyze and systematize the contradictory rights and responsibilities, powers and positions of subjects of tax relations, to identify problems and reserves of elimination of the specified contradictions. The main employed method is the method of comparative analysis. The logistic approach is also used to establish the communication of subjects of tax relations in integrated tax system; factor analysis is used to establish the causes of conflict in the interaction of the subjects of tax relations, and system approach is for generalization of results of researches. It is shown that the main reason of opposition of tax authorities and taxpayers is the positional antagonism regarding compulsory payment of taxes, and the tax control methodology of compliance with the law concerning taxes and fees used by tax authorities. As the reasons of disagreements between regulatory authorities in the tax system (tax authorities, police, the Investigative committee at Prosecutor’s office of the Russian Federation) are produced departmental contradiction during tax audits and investigative actions, and also legislative uncertainty of differentiation of their powers. The model of interaction of subjects of tax relations on the equal relations basis, which supposed legislatively installed system of punishments for tax offenses for all participants of tax system, including supervisory authorities, is offered as the solution of the revealed problem as part of the research. Results of the research can be useful to legislators, supervisory authorities of tax system, taxpayers, tax agents in order to overcome tax disagreements, and also the researchers specializing in area of conflict management. Results of the research are under consideration in the Interregional inspectorate of the Federal Tax Service of Russia of Ural federal district. Keywords: subjects of tax relations, problems of interaction, positional antagonism, regulatory authorities, departmental conflicts, tax audits JEL Classifications: H23, H32